2015
DOI: 10.5006/1432
|View full text |Cite
|
Sign up to set email alerts
|

Volta Potentials Measured by Scanning Kelvin Probe Force Microscopy as Relevant to Corrosion of Magnesium Alloys

Abstract: The relative electrochemical properties of second phases compared to the surrounding matrix gives rise to localization of corrosion on magnesium (Mg) alloys. Localized corrosion and its subsequent propagation in Mg alloys is largely driven by so-called ‘microgalvanic coupling’ of microstructural constituents within the alloy microstructure. In the present work, atomic force microscopy (AFM) imaging coupled with scanning Kelvin probe force microscopy (SKPFM) were used to generate surface Volta potential maps of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…17,18 Recently this approach has been increasingly used in corrosion studies of various alloys. [19][20][21][22] However, due to variations in the experimental conditions, such as sample surface preparations prior to SKPFM measurements, there is lack of reproducibility of reported Volta potential data measured by different research groups. 23,24 Meanwhile, a large divergence in experimental Volta potential data has been found especially for less noble IMPs in Al-alloys, such as Al 2 CuMg and Mg 2 Si, 14,25 resulting in different conclusions from such studies.…”
mentioning
confidence: 99%
“…17,18 Recently this approach has been increasingly used in corrosion studies of various alloys. [19][20][21][22] However, due to variations in the experimental conditions, such as sample surface preparations prior to SKPFM measurements, there is lack of reproducibility of reported Volta potential data measured by different research groups. 23,24 Meanwhile, a large divergence in experimental Volta potential data has been found especially for less noble IMPs in Al-alloys, such as Al 2 CuMg and Mg 2 Si, 14,25 resulting in different conclusions from such studies.…”
mentioning
confidence: 99%
“…SKPFM measurements were obtained prior to SEM/EDS characterization of the same regions on both braze alloy joints to avoid any effect of electron irradiation on surface potential measurements [22,26,27]. Potential maps acquired from SKPFM coupled with composition maps obtained from SEM/EDS clearly showed that the observed variations in potential correlated with changes in composition within the braze regions (Figures 8 and 9).…”
Section: Skpfm Measurementsmentioning
confidence: 97%
“…The second pass is then used to measure the tip-sample surface potential difference at a user-determined fixed lift height above the sample surface. The SKPFM technique and important experimental considerations have been described in greater detail previously [22], but lift heights of~100 nm and a frequency modulation based detection scheme were employed. To enhance signal to noise and minimize the effects of residual sample roughness on the surface potential image, a slow scan rate was used (~0.05-0.1 Hz).…”
Section: Scanning Kelvin Probe Force Microscopy (Skpfm) Of Brazed Regmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Scanning Kelvin Probe Force Microscopy (SKPFM) SKPFM imaging was conducted using a Bruker Dimension Icon AFM operating in frequency modulation (FM) PeakForce KPFM mode. [10][11][12] After polishing, each test coupon was cleaned with UHP N 2 prior to imaging to remove any loose surface particulates. A PeakForce amplitude of 75 nm and a lift height of 85 nm were used to acquire the topography and surface potential images, respectively.…”
Section: Alloys and Sample Preparationmentioning
confidence: 99%